Molecular mechanisms induced by phase modifiers used in hydrometallurgy: consequences on transfer efficiency and process safety - El Maangar, Asmae; Prévost, Sylvain; Dourdain, Sandrine; Zemb, Thomas (Comptes Rendus. Chimie)
It is a matter of strategic independence for many countries to urgently find processes that take into account environmental and economic issues when recycling critical metals. Liquid–liquid (L/L) extraction is a promising method for recovering rare-earth elements from electrical and electronic waste. However, an optimized process on an industrial scale has not yet been established. One of the main reasons is the lack of fundamental knowledge. Therefore, designing a cost-effective and adaptive formulation is still beyond the scope of possibilities. This requires deciphering the molecular forces that control ion transfer beyond the classical supramolecular complexation and developing predictive models compatible with the design and control needs of recycling processes. In all liquid/liquid processes, the high loading of the organic solvent with metal salts/acids or extractant can sometimes lead to a third phase formation. Phase modifiers are often added to the solvent phase in order to prevent the formation of this third phase. However, the effect of these additives on the extraction efficiency as well as their mechanisms of action are still poorly understood. The phase modifiers used in industrial processes are mainly fatty alcohols, called “lipotropes”. In this paper, we study a new class of molecules opening new possibilities beyond the commonly used phase modifiers (i.e., n-octanol). These are the “hydrotropic” molecules. We first show the role of a model hydrotrope (PnP) in preventing the third phase formation for different extraction systems. We also show that the role of modifiers can be understood according to three molecular mechanisms: as co-solvent, as co-surfactant and by preferential solvation. The dominant molecular effect can be identified and quantified by combining surface tension and neutron scattering experiments. In the case of phase modifiers that are hydrotropes, the co-solvent or co-surfactant effect is dominant. In the case of “lipotropes”, the preferential solvation mechanism is emphasized. Finally, the consequences of these mechanisms on the extraction efficiency and selectivity are discussed.